The taxation of black economic empowerment transactions, with specific reference to the financial sector - Kamlana, Unathi (Rhodes University, Faculty of Commerce, Department of Accounting, 2006)
There has been some concern that the pace of expectations being built up regarding the transfer of ownership of the economy into the hands of the previously disadvantaged was not allowing for the due diligence and analysis of the implications of such transactions. Tax legislation relating to the transfer of assets is also not seen to be consistently conducive to this process. The focus of this thesis is taxation and a critical analysis of how the current tax legislation affects most of the transactions which usually form the basis of black economic empowerment. It is argued that tax policy is one of the fundamental instruments available to government to encourage the process of black economic empowerment. It is therefore important to assess whether or not current tax legislation is supportive of the process of black economic empowerment and to suggest ways in which it can be amended to serve this purpose. By means of a literature review and a case study of a Black Economic Empowerment deal in the financial sector, the thesis examines various sections of the Income Tax Act, 58 of 1962, which may have a bearing on black economic empowerment transactions and structures, including corporate restructuring rules, the taxation of trusts, inter-company loans, the use of hybrid financial instruments, the taxation of small business corporations, employee share incentive schemes, connected persons rules and value-shifting arrangements, the general deduction formula and the deductibility of interest incurred on amounts raised to acquire shares. It appears that although some aspects of the current tax legislation lend themselves to assisting black economic empowerment transactions, there are still areas where much improvement is required.,KMBT_363
Keywords: Black people -- South Africa -- Economic conditions; Business enterprises, Black -- Taxation -- South Africa; Employee empowerment -- South Africa; Income tax -- Law and legislation -- South Africa